Thermally conductive sheet and method for manufacturing the same, and method for mounting the thermally conductive sheet

The thermally conductive sheet with a fibrous filler and uncured adhesive resin addresses thermal resistance and adhesion issues, offering improved workability and reworkability by becoming sticky under load and recovering thickness, enhancing heat dissipation in electronic components.

CN112368827BActive Publication Date: 2024-12-27SEKISUI CHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980045523.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-07-18
Filing Date
2019-07-04
Publication Date
2024-12-27
Estimated Expiration
2039-07-04

AI Technical Summary

Technical Problem

The challenge is to improve the heat dissipation characteristics of thermally conductive sheets by reducing thermal resistance, enhancing adhesion to electronic components, ensuring good workability, and providing reworkability, while addressing issues of unevenness and poor adhesion during installation.

Method used

A thermally conductive sheet with a fibrous filler protruding from the surface, covered by an uncured adhesive resin, which becomes sticky under load to enhance adhesion and recovers thickness upon load release, maintaining operability and reworkability.

Benefits of technology

The sheet achieves reduced thermal resistance, improved adhesion, and excellent reworkability by minimizing stickiness before installation and ensuring consistent adhesion and handling properties during and after load application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112368827B_ABST
    Figure CN112368827B_ABST
Patent Text Reader

Abstract

Provided are a thermally conductive sheet having excellent adhesion to electronic components, operability, and reworkability, and a method for manufacturing the same and a method for mounting the thermally conductive sheet. The sheet has a sheet body 2 formed by curing a binder resin, the binder resin at least containing a polymer matrix component and a fibrous thermally conductive filler 10, the volume ratio of the fibrous thermally conductive filler 10 to the binder resin being 0.6 or less when the binder resin is set to 1, and the fibrous thermally conductive filler 10 protrudes from the surface of the sheet body 2 and is covered with an uncured component of the binder resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present technology relates to a thermally conductive sheet that is attached to electronic components and improves their heat dissipation. This application claims priority based on Japanese Patent Application No. 2018-134769 filed in Japan on July 18, 2018, which is incorporated herein by reference. Background Art

[0002] Conventionally, semiconductor elements mounted on various electrical devices such as personal computers and other devices generate heat due to driving. If the generated heat is accumulated, it will have an adverse effect on the driving of the semiconductor element and peripheral devices, so various cooling methods are used. As cooling methods for electronic components such as semiconductor elements, there are known methods of installing a fan on the device to cool the air in the device housing, and installing a heat sink such as a heat sink or a heat sink on the semiconductor element to be cooled.

[0003] When a heat sink is installed on a semiconductor element for cooling, a thermally conductive sheet is provided between the semiconductor element and the heat sink in order to efficiently discharge the heat of the semiconductor element. As a thermally conductive sheet, a thermally conductive sheet containing a filler such as a thermally conductive filler such as carbon fiber dispersed in a silicone resin is widely used (see Patent Document 1). It is known that these thermally conductive fillers have thermal anisotropy. For example, when carbon fiber is used as a thermally conductive filler, the thermal conductivity in the fiber direction is about 600W / m·K to 1200W / m·K. When boron nitride is used, the thermal conductivity in the surface direction is about 110W / m·K and in the direction perpendicular to the surface direction is about 2W / m·K, and it has anisotropy.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-023335

[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-029076

[0008] Patent Document 3: Japanese Patent Application Publication No. 2015-029075 Summary of the invention

[0009] Problems to be solved by the invention

[0010] Here, the heat dissipation of electronic components such as CPUs of personal computers tends to increase year by year as they become faster and more powerful. However, in contrast, with the advancement of micro-silicon circuit technology, the size of chips such as processors has become the same size or smaller than before, and the heat flow rate per unit area has increased. Therefore, in order to avoid adverse conditions caused by this temperature rise, it is required to dissipate heat and cool electronic components such as CPUs more effectively.

[0011] In order to improve the heat dissipation characteristics of the thermally conductive sheet, it is required to reduce the thermal resistance, which is an index indicating the difficulty of heat conduction. In order to reduce the thermal resistance, it is effective to improve the adhesion to heat dissipation parts such as electronic components and heat dissipation devices as heat generating bodies and to reduce the thermal resistance by making the thermally conductive sheet thinner.

[0012] When the thermally conductive molded body is thinly cut to form a thermally conductive sheet, the surface of the cut sheet has unevenness and lacks adhesion to the electronic components. If the adhesion is poor, the sheet will fall off the component due to poor adhesion to the component during the installation process. In addition, due to poor adhesion to the electronic components as heat generating bodies and heat dissipation bodies such as heat dissipation devices, air may be contained and the thermal resistance may not be sufficiently reduced.

[0013] To address this problem, a technique has been proposed in which the surface of a thermally conductive sheet produced by cutting a thermally conductive molded body is pressed or allowed to stand for a long time to allow uncured components of the binder resin to seep out of the surface, thereby improving the adhesion between the thermally conductive sheet and the electronic component (see Patent Documents 2 and 3).

[0014] On the other hand, if the uncured components of the adhesive resin ooze out on the sheet surface, tackiness is imparted, thereby causing a problem of poor workability. Therefore, a thermally conductive sheet that has tackiness (adhesiveness) when mounting electronic components but whose tackiness decreases before mounting is preferred.

[0015] In addition, the thermally conductive sheet is also required to have reworkability, that is, to correct the positional deviation of the electronic component and the heat dissipation member during assembly, or to be able to be disassembled for some reason after temporary assembly and reassembled, etc. That is, after a load is applied by sandwiching the thermally conductive sheet between the electronic component and the heat dissipation member, even after the load is removed, it is preferred that the thermally conductive sheet exhibits the same viscosity as before the load is applied and can be attached to the electronic component, and maintains the same operability and adhesion as before the load is applied.

[0016] Therefore, an object of the present technology is to provide a thermally conductive sheet having excellent adhesion to electronic components, handleability, and reworkability, a method for producing the sheet, and a method for mounting the thermally conductive sheet.

[0017] Methods for solving problems

[0018] In order to solve the above-mentioned problems, the thermally conductive sheet involved in the present technology has a sheet body formed by curing an adhesive resin, and the adhesive resin contains at least a polymer matrix component and a fibrous thermally conductive filler. The volume ratio of the fibrous thermally conductive filler to the adhesive resin is less than 0.6 when the adhesive resin is set to 1. The fibrous thermally conductive filler protrudes from the surface of the sheet body and is covered with the uncured component of the adhesive resin.

[0019] In addition, the method for manufacturing a thermally conductive sheet involved in the present technology includes the following steps: a step of molding a thermally conductive resin composition containing a fibrous thermally conductive filler in a binder resin into a predetermined shape and curing it to form a thermally conductive molded body, and a step of cutting the above-mentioned thermally conductive molded body into sheets to form a thermally conductive sheet; the volume ratio of the above-mentioned fibrous thermally conductive filler to the above-mentioned binder resin is 0.6 or less when the binder resin is set to 1, and the above-mentioned fibrous thermally conductive filler protrudes from the surface of the above-mentioned sheet body and is covered with the uncured component of the above-mentioned binder resin.

[0020] In addition, the thermally conductive sheet installation method involved in the present technology is a thermally conductive sheet installation method placed on an electronic component and sandwiched between a heat dissipation member, which has the following steps: when placed on the above-mentioned electronic component, the thermally conductive sheet exhibits viscosity by applying a load to the above-mentioned thermally conductive sheet and is attached to the electronic component, and when the above-mentioned thermally conductive sheet is re-attached, the load is released, the sheet is peeled off from the above-mentioned electronic component, and is attached to the above-mentioned electronic component again; the above-mentioned thermally conductive sheet has a sheet body formed by curing an adhesive resin, the adhesive resin contains at least a polymer matrix component and a fibrous thermally conductive filler, the volume ratio of the above-mentioned fibrous thermally conductive filler to the above-mentioned adhesive resin is 0.6 or less when the adhesive resin is set to 1, and the above-mentioned fibrous thermally conductive filler protrudes from the surface of the above-mentioned sheet body and is covered with an uncured component of the above-mentioned adhesive resin.

[0021] Effects of the Invention

[0022] According to the present technology, the fibrous thermally conductive filler is made to protrude on the sheet surface, thereby reducing or eliminating the stickiness. In addition, when a load is applied to the sheet body during actual use, the sheet becomes sticky. Therefore, the thermally conductive sheet has good operability and workability by reducing or eliminating the stickiness before installation, and by becoming sticky during installation, the sheet has improved adhesion with electronic components and heat dissipation components even when the sheet surface has unevenness, thereby reducing thermal resistance.

[0023] Furthermore, when the applied load of the thermally conductive sheet is released, the sheet body recovers to 90% or more of its thickness. At this time, the viscosity decreases or disappears. Therefore, even when the thermally conductive sheet is reinstalled, the handling and adhesion are not changed from the initial state, and the reworkability is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] [ Figure 1 ] Figure 1 This is a cross-sectional view showing a thermally conductive sheet to which the present technique is applied.

[0025] [ Figure 2 ] Figure 2 This is a perspective view showing an example of a step of cutting a thermally conductive molded body.

[0026] [ Figure 3 ] Figure 3 This is a cross-sectional view showing a step of pressing the thermally conductive sheet to which the release film is attached.

[0027] [ Figure 4 ] Figure 4 is a cross-sectional view showing an example of a semiconductor device. DETAILED DESCRIPTION

[0028] Hereinafter, a thermally conductive sheet and a method for manufacturing the same, and a method for mounting the thermally conductive sheet to which the present technology is applied will be described with reference to the attached drawings. Figure 1 The following detailed description will be given. In addition, of course, the present technology is not limited to the following embodiments, and various changes can be made without departing from the main purpose of the present technology. In addition, the drawings are schematic, and sometimes the ratios of various dimensions are different from the actual ratios. Specific dimensions should be judged with reference to the following description. In addition, of course, the parts where the dimensional relationships and ratios between the drawings are different are also included.

[0029] The thermally conductive sheet to which the present technology is applied has a sheet body formed by curing a binder resin, the binder resin containing at least a polymer matrix component and a fibrous thermally conductive filler. In addition, in the thermally conductive sheet, the volume ratio of the fibrous thermally conductive filler to the binder resin is 0.6 or less when the binder resin is set to 1. In addition, the fibrous thermally conductive filler protrudes from the surface of the sheet body and is covered by the uncured component of the binder resin.

[0030] In such a thermally conductive sheet, the fibrous thermally conductive filler protrudes on the sheet surface, thereby reducing or eliminating the viscosity. In addition, in actual use, if a load is applied to the sheet body by pressing it in advance or by clamping it between an electronic component and a heat dissipation member, the fibrous thermally conductive filler protruding on the sheet surface is buried in the sheet body, and the uncured components of the adhesive resin carried in the sheet body ooze out, thereby showing viscosity. Therefore, the thermally conductive sheet has good operability and workability by reducing or eliminating the viscosity before installation, and by showing viscosity during installation, even if the sheet surface has unevenness, the closeness with the electronic component and the heat dissipation member is improved, thereby reducing thermal resistance.

[0031] In addition, the thermally conductive sheet has a volume ratio of the fibrous thermally conductive filler to the binder resin of 0.6 or less when the binder resin is set to 1, so that after a load is applied when mounting on an electronic component, even when the load is released for reasons such as correcting positional deviation, the sheet body recovers to a thickness of 90% or more. At this time, the fibrous thermally conductive filler buried in the sheet body protrudes again on the sheet surface, and the viscosity decreases or disappears. Therefore, even when the thermally conductive sheet is provided for reinstallation, the handling and adhesion are not changed compared to the initial state, and the reprocessability is excellent.

[0032] [Thermal conductive sheet]

[0033] Figure 1 A thermally conductive sheet 1 to which the present technique is applied is shown. The thermally conductive sheet 1 has a sheet body 2 formed by curing a binder resin containing at least a polymer matrix component and a fibrous thermally conductive filler.

[0034] On the surface 2a of the sheet body 2, a fibrous thermally conductive filler 10 described later protrudes. As a result, the viscosity of the thermally conductive sheet 1 is reduced or eliminated. Here, the viscosity is reduced or eliminated, which means that the viscosity is reduced to a level where the stickiness is not felt when a person touches it, thereby improving the operability and workability of the thermally conductive sheet 1. In the thermally conductive sheet 1, some uncured components 11 of the binder resin seep out from the sheet body 2 and cover the thermally conductive filler 10 protruding from the surface. However, as described in detail later, the thermally conductive filler 10 protrudes from the sheet surface by a predetermined length or more, thereby reducing or eliminating the viscosity.

[0035] (Polymer matrix component)

[0036] The polymer matrix component constituting the sheet body 2 is a polymer component serving as a base material of the thermally conductive sheet 1. The type thereof is not particularly limited, and a known polymer matrix component can be appropriately selected. For example, a thermosetting polymer is one example of a polymer matrix component.

[0037] As the above-mentioned thermosetting polymer, for example, crosslinked rubber, epoxy resin, polyimide resin, bismaleimide resin, benzocyclobutene resin, phenolic resin, unsaturated polyester, diallyl phthalate resin, silicone resin, polyurethane, polyimide silicone, thermosetting polyphenylene ether, thermosetting modified polyphenylene ether, etc. can be mentioned. These can be used alone or in combination of two or more.

[0038] In addition, examples of the crosslinked rubber include natural rubber, butadiene rubber, isoprene rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-propylene rubber, chlorinated polyethylene, chlorosulfonated polyethylene, butyl rubber, halogenated butyl rubber, fluororubber, urethane rubber, acrylic rubber, polyisobutylene rubber, silicone rubber, etc. These may be used alone or in combination of two or more.

[0039] Among these thermosetting polymers, silicone resins are preferably used because they are excellent in molding processability and weather resistance, and have good adhesion and conformability to electronic components. The silicone resin is not particularly limited, and the type of silicone resin can be appropriately selected according to the purpose.

[0040] From the viewpoint of obtaining the above-mentioned molding processability, weather resistance, adhesion, etc., the above-mentioned silicone resin is preferably a silicone resin composed of a main agent of liquid silicone gel and a curing agent. Examples of such silicone resins include addition reaction type liquid silicone resins and heat-curable millable silicone resins that use peroxide for vulcanization. Among them, as a heat dissipation component of an electronic device, the heat-generating surface of the electronic component and the heat dissipation device surface are required to have good adhesion, so addition reaction type liquid silicone resins are particularly preferred.

[0041] As the addition reaction type liquid silicone resin, it is preferable to use a two-component addition reaction type silicone resin having a polyorganosiloxane having a vinyl group as a main agent and a polyorganosiloxane having a Si—H group as a curing agent.

[0042] Here, the liquid silicone component includes a silicone liquid A component as a main agent and a silicone liquid B component including a curing agent, and the mixing ratio of the silicone liquid A component to the silicone liquid B component is preferably a silicone liquid A component containing more silicone liquid B than silicone liquid B. Thus, in the thermally conductive sheet 1, flexibility can be imparted to the sheet body 2, and the uncured components of the binder resin (polymer matrix component) can be exuded on the surfaces 2a and 2b of the sheet body 2 by the pressing process, thereby exhibiting stickiness.

[0043] In addition, by setting the volume ratio of the content of the above-mentioned polymer matrix component and the fibrous thermally conductive filler in the thermally conductive sheet of the present invention to be 0.6 or less when the polymer matrix component is set to 1, the recovery rate after the removal of the applied load can be made to be 90% or more, and reprocessability can be achieved as described later.

[0044] [Fiber-shaped thermally conductive filler]

[0045] The fibrous thermally conductive filler included in the thermally conductive sheet 1 is a component for improving the thermal conductivity of the sheet. The type of the thermally conductive filler is not particularly limited as long as it is a fibrous material with high thermal conductivity, but carbon fibers are preferably used in order to obtain higher thermal conductivity.

[0046] In addition, the thermally conductive filler may be used alone or in combination of two or more. In addition, when two or more thermally conductive fillers are used, they may all be fibrous thermally conductive fillers or a fibrous thermally conductive filler may be mixed with a thermally conductive filler of another shape.

[0047] There is no particular limitation on the type of carbon fiber, and it can be appropriately selected according to the purpose. For example, it is possible to use a carbon fiber obtained by graphitizing a pitch-based, PAN-based, PBO-based fiber, or a carbon fiber synthesized by an arc discharge method, a laser evaporation method, a CVD method (chemical vapor growth method), or a CCVD method (catalyst chemical vapor growth method). Among these, from the perspective of obtaining high thermal conductivity, a carbon fiber obtained by graphitizing a PBO fiber or a pitch-based carbon fiber is more preferred.

[0048] In addition, the carbon fibers may be partially or entirely surface treated as required before use. Examples of the surface treatment include oxidation, nitridation, nitration, sulfonation, or treatments for attaching or bonding metals, metal compounds, organic compounds, etc. to the functional groups introduced to the surface by these treatments or to the surface of the carbon fibers. Examples of the functional groups include hydroxyl, carboxyl, carbonyl, nitro, and amino groups.

[0049] Furthermore, the average fiber length (average major axis length) of the above-mentioned carbon fibers can be appropriately selected without particular restrictions. From the perspective of ensuring high thermal conductivity, the average fiber length is preferably in the range of 50 μm to 300 μm, more preferably in the range of 75 μm to 275 μm, and particularly preferably in the range of 90 μm to 250 μm.

[0050] Furthermore, the average fiber diameter (average minor axis length) of the carbon fibers can be appropriately selected without particular limitation, but is preferably in the range of 4 μm to 20 μm, more preferably in the range of 5 μm to 14 μm, from the perspective of reliably obtaining high thermal conductivity.

[0051] The aspect ratio (average major axis length / average minor axis length) of the carbon fibers is preferably 8 or more, and more preferably 9 to 30, from the perspective of reliably obtaining high thermal conductivity. If the aspect ratio is less than 8, the fiber length (major axis length) of the carbon fibers is short, so there is a concern that thermal conductivity may decrease. On the other hand, if the aspect ratio exceeds 30, dispersibility in the thermally conductive sheet decreases, so there is a concern that sufficient thermal conductivity may not be obtained.

[0052] Here, the average major axis length and the average minor axis length of the carbon fibers can be measured, for example, using a microscope, a scanning electron microscope (SEM), or the like, and the average can be calculated from a plurality of samples.

[0053] In addition, the content of the fibrous thermally conductive filler in the thermally conductive sheet 1 is not particularly limited as long as the volume ratio relative to the polymer matrix component is 0.6 or less, and can be appropriately selected according to the purpose, preferably 4 volume % to 40 volume %, more preferably 5 volume % to 35 volume %. If the content is less than 4 volume %, it may be difficult to obtain a sufficiently low thermal resistance, and if it exceeds 40 volume %, it may affect the moldability of the thermally conductive sheet 1 and the orientation of the fibrous thermally conductive filler. In addition, the content of the thermally conductive filler including the fibrous thermally conductive filler in the thermally conductive sheet 1 is preferably 15 volume % to 75 volume %.

[0054] [Sheet surface protrusion / silicone coating]

[0055] The fibrous thermally conductive filler protrudes from the surface of the sheet body 2 and is covered with the uncured component of the binder resin. The length of the fibrous thermally conductive filler protruding from the surface of the sheet body 2 is preferably longer than 50 μm. Thus, the tackiness is reduced or eliminated before the thermally conductive sheet 1 is attached, and workability and operability can be improved.

[0056] In the thermally conductive sheet 1, the fibrous thermally conductive filler is coated with the uncured component, thereby reducing the contact thermal resistance when mounted on an electronic component or the like. In addition, in the thermally conductive sheet 1, the uncured component of the binder resin exists on the surface 2a of the sheet body 2, but the fibrous thermally conductive filler is protruded, so that the finger does not feel sticky during operation, and when mounted on an electronic component or the like, operations such as attachment and position alignment become possible.

[0057] The length of the fibrous thermally conductive filler protruding from the surface of the sheet body 2 refers to the length from the base to the tip of the fibrous thermally conductive filler protruding from the surface of the sheet body 2. In the thermally conductive sheet 1, the viscosity can be reduced or eliminated by making all the fibrous thermally conductive fillers protrude from the surface of the sheet body 2 longer than 50 μm, and the length can be appropriately adjusted according to the amount of the fibrous thermally conductive filler protruding from the surface 2a of the sheet body 2 in the step of cutting into sheets described later.

[0058] [Inorganic fillers]

[0059] The thermally conductive sheet 1 may further contain an inorganic filler as a thermally conductive filler. By containing an inorganic filler, the thermal conductivity of the thermally conductive sheet 1 can be further improved, and the strength of the sheet can be improved. As the above-mentioned inorganic filler, there is no particular limitation on the shape, material, average particle size, etc., and it can be appropriately selected according to the purpose. As the above-mentioned shape, for example, spherical, elliptical, blocky, granular, flat, needle-shaped, etc. can be cited. Among them, from the perspective of filling, spherical and elliptical shapes are preferred, and spherical shapes are particularly preferred.

[0060] As the material of the above-mentioned inorganic filler, for example, aluminum nitride (aluminum nitride: AlN), silicon dioxide, aluminum oxide (aluminum trioxide), boron nitride, titanium dioxide, glass, zinc oxide, silicon carbide, silicon element (silicon), silicon oxide, metal particles, etc. can be cited. They can be used alone or in combination of two or more. Among these, aluminum oxide, boron nitride, aluminum nitride, zinc oxide, and silicon dioxide are preferred, and aluminum oxide and aluminum nitride are particularly preferred from the perspective of thermal conductivity.

[0061] The inorganic filler may be a surface-treated inorganic filler. If the inorganic filler is treated with a coupling agent as the surface treatment, the dispersibility of the inorganic filler is improved, and the flexibility of the thermally conductive sheet is improved.

[0062] The average particle size of the inorganic filler can be appropriately selected according to the type of inorganic material, etc. When the inorganic filler is alumina, the average particle size is preferably 1 μm to 10 μm, more preferably 1 μm to 5 μm, and particularly preferably 4 μm to 5 μm. If the average particle size is less than 1 μm, there is a concern that the viscosity becomes high and mixing becomes difficult. On the other hand, if the average particle size exceeds 10 μm, there is a concern that the thermal resistance of the thermally conductive sheet 1 becomes high.

[0063] Furthermore, when the inorganic filler is aluminum nitride, the average particle size is preferably 0.3 μm to 6.0 μm, more preferably 0.3 μm to 2.0 μm, and particularly preferably 0.5 μm to 1.5 μm. If the average particle size is less than 0.3 μm, the viscosity may increase and mixing may become difficult. If it exceeds 6.0 μm, the thermal resistance of the thermally conductive sheet 1 may increase.

[0064] The average particle size of the inorganic filler can be measured, for example, using a particle size distribution meter or a scanning electron microscope (SEM).

[0065] [Other ingredients]

[0066] In addition to the polymer matrix component and the fibrous thermally conductive filler and the inorganic filler appropriately contained in the thermally conductive sheet 1, other components may be appropriately contained according to the purpose. Examples of other components include magnetic metal powder, thixotropy imparting agent, dispersant, curing accelerator, retarder, micro-thickener, plasticizer, flame retardant, antioxidant, stabilizer, colorant, etc. In addition, electromagnetic wave absorption performance can be imparted to the thermally conductive sheet 1 by adjusting the content of the magnetic metal powder.

[0067] [Method for producing thermally conductive sheet]

[0068] Next, the manufacturing process of the thermally conductive sheet 1 is described. The manufacturing process of the thermally conductive sheet 1 to which the present technology is applied includes the following steps: a step of forming a thermally conductive molded body by molding a thermally conductive resin composition containing a fibrous thermally conductive filler in a binder resin into a predetermined shape and curing the composition (step A); a step of cutting the thermally conductive molded body into sheets to form a thermally conductive sheet (step B); and a step of pressing the thermally conductive sheet as needed to cause the uncured components of the binder resin to ooze out (step C).

[0069] [Process A]

[0070] In this step A, the polymer matrix component, the fibrous thermally conductive filler, the appropriately contained inorganic filler, and other components are mixed to prepare a thermally conductive resin composition. As described above, in the method for producing a thermally conductive sheet using the present technology, the volume ratio of the fibrous thermally conductive filler to the binder resin is adjusted to be 0.6 or less when the binder resin is set to 1. In addition, the steps of mixing and preparing the components are not particularly limited. For example, the thermally conductive resin composition can be prepared by adding the fibrous thermally conductive filler, the appropriately added inorganic filler, the magnetic metal powder, and other components to the polymer matrix component and mixing them.

[0071] Next, a fibrous thermally conductive filler such as carbon fiber is oriented in one direction. As long as the filler is oriented in one direction, the method is not particularly limited. For example, by extruding or pressing the thermally conductive resin composition into a hollow mold with a high shear force, the fibrous thermally conductive filler can be oriented in one direction relatively easily, and the orientation of the fibrous thermally conductive filler becomes the same (within ±10°).

[0072] As a method of extruding or pressing the thermally conductive resin composition into the hollow mold with high shear force, specifically, an extrusion molding method or a mold molding method can be cited. When the thermally conductive resin composition is extruded from the mold in the extrusion molding method, or when the thermally conductive resin composition is pressed into the mold in the mold molding method, the thermally conductive resin composition flows, and the fibrous thermally conductive filler is oriented along the flow direction. At this time, if a slit is installed at the front end of the mold, the fibrous thermally conductive filler becomes easier to be oriented.

[0073] The thermally conductive resin composition extruded or pressed into a hollow mold is molded into a bulk shape corresponding to the shape and size of the mold, and the polymer matrix component is cured while maintaining the orientation state of the fibrous thermally conductive filler, thereby forming a thermally conductive molded body. The thermally conductive molded body refers to a base material (molded body) for sheet cutting, which is the basis for the thermally conductive sheet 1 obtained by cutting into a predetermined size.

[0074] The size and shape of the hollow mold and the thermally conductive molded body can be determined according to the required size and shape of the thermally conductive sheet 1, and can be, for example, a rectangular parallelepiped having a longitudinal dimension of 0.5 cm to 15 cm and a lateral dimension of 0.5 cm to 15 cm. The length of the rectangular parallelepiped can be determined as required.

[0075] The method and conditions for curing the polymer matrix component can be changed according to the type of the polymer matrix component. For example, when the polymer matrix component is a thermosetting resin, the curing temperature during thermal curing can be adjusted. Furthermore, when the thermosetting resin is a thermosetting resin containing a main component of liquid silicone gel and a curing agent, it is preferably cured at a curing temperature of 80°C to 120°C. In addition, there is no particular limitation on the curing time during thermal curing, and it can be set to 1 hour to 10 hours.

[0076] Here, in step A, not all of the polymer matrix component is cured, but uncured components are also carried. The uncured components ooze out on the surface of the sheet by pressing the thermally conductive sheet, and can impart tackiness to the sheet surface.

[0077] [Process B]

[0078] like Figure 2 As shown in FIG. 1 , in step B of cutting the thermally conductive molded body 6 into a sheet to form the thermally conductive sheet 1, the thermally conductive molded body 6 is cut into a sheet so that the angle with respect to the long axis direction of the oriented fibrous thermally conductive filler is 0° to 90°. Thus, the thermally conductive filler 10 is oriented in the thickness direction of the sheet body.

[0079] The thermally conductive molded body 6 can be cut using a cutting device. The cutting device is not particularly limited as long as it is a method that can cut the thermally conductive molded body 6, and a known cutting device can be used as appropriate. For example, an ultrasonic cutter, a planer, etc. can be used.

[0080] The cut thickness of the thermally conductive molded body 6 is the thickness of the sheet body 2 of the thermally conductive sheet 1 , and can be appropriately set according to the application of the thermally conductive sheet 1 , and is, for example, 0.5 to 3.0 mm.

[0081] In the step B, a plurality of thermally conductive sheets 1 may be cut into small pieces by introducing scores into the thermally conductive sheets 1 cut out from the thermally conductive molded body 6 .

[0082] In the thermally conductive sheet 1 manufactured through the above steps, the fibrous thermally conductive filler protrudes on the surface of the sheet body 2 as the cut surface, and the stickiness is reduced or eliminated. Thus, the handling and workability of the thermally conductive sheet 1 are improved.

[0083] [Process C]

[0084] The manufacturing process of the thermally conductive sheet 1 may include, if necessary, a step C of causing uncured components of the binder resin to seep out by pressing the thermally conductive sheet 1. Thus, both surfaces of the thermally conductive sheet 1 can be entirely covered with uncured components of the binder resin seeping out from the sheet body 2, thereby exhibiting adhesiveness.

[0085] The pressing may be performed, for example, using a pair of pressing devices consisting of a flat plate and a flat-surface pressing head. Alternatively, the pressing may be performed using a nip roller.

[0086] There is no particular restriction on the pressure during the above-mentioned pressing, and it can be appropriately selected according to the purpose. If it is too low, there is a tendency for the thermal resistance to remain unchanged compared to the case where no pressing is performed. If it is too high, there is a tendency for the sheet to stretch. Therefore, it is preferably set to a pressure range of 0.1MPa to 100MPa, and more preferably set to a pressure range of 0.5MPa to 95MPa.

[0087] Here, as described above, the thermally conductive molded body is not entirely cured in the polymer matrix component, but the molded body sheet carries uncured components of the binder resin (polymer matrix component) in the sheet body, and a portion of the uncured components is efficiently exuded to the sheet surface by the pressing process. Thus, the thermally conductive sheet 1 has tackiness on the sheet surface.

[0088] Furthermore, by passing through the pressing step, the thermally conductive sheet 1 carries the uncured component of the binder resin on the surface 2 a , thereby increasing the adhesiveness of the thermally conductive sheet 1 and reducing the interface contact resistance under a light load.

[0089] Thus, according to the present technology, a sheet can be cut thinly, and even if the sheet body does not contain a large amount of uncured components of the adhesive resin, the uncured components can be exuded over the entire surface of the sheet surface for coating. In addition, the curing of the adhesive resin is progressing, and the sheet is relatively hard and has excellent shape retention. On the other hand, even if the sheet body does not contain a large amount of uncured components of the adhesive resin, the uncured components can be exuded over the entire surface of the sheet surface for coating.

[0090] Therefore, according to the thermally conductive sheet manufactured by this technology, regardless of the unevenness of the sheet surface, it is possible to improve the adhesion with electronic components and heat dissipation components and reduce thermal resistance. In addition, with respect to the thermally conductive sheet manufactured by this technology, it is not necessary to apply an adhesive for adhesion with electronic components and heat dissipation components to the sheet surface, and the thermal resistance of the sheet does not increase. Furthermore, for the thermally conductive sheet containing a thermally conductive filler in the adhesive resin, it is possible not only to reduce the thermal resistance from the low load area, but also to improve the excellent viscosity (adhesion), installation and thermal characteristics.

[0091] [Release film]

[0092] In addition, in the above-mentioned step C, if Figure 3 As shown, the thermal conductive sheet 1 is preferably pressed with a plastic film 11 attached to at least one side, preferably both sides. As the plastic film, for example, a PET film can be used. The plastic film may be subjected to a release treatment on the side attached to the surface of the molded body sheet.

[0093] By attaching the plastic film 11 to the surface of the sheet body 2 of the thermally conductive sheet 1, the uncured components that seep out to the sheet surface during the pressing process can be retained on the sheet surface by the tension acting between the plastic film 11, thereby forming a resin coating layer covering the entire sheet surface.

[0094] In addition, when the thermally conductive sheet 1 is actually used, the plastic film is peeled off to expose the sheet surface having adhesiveness, and the sheet is provided for mounting on electronic components or the like.

[0095] [Example of use]

[0096] In actual use, the plastic film 11 of the thermally conductive sheet 1 is appropriately peeled off and mounted inside electronic components such as semiconductor devices or various electronic devices. In this case, the thermally conductive sheet 1 has excellent handling properties because the stickiness of the sheet body 2 is reduced or eliminated or the plastic film 11 is attached to the surface of the sheet body 2. Moreover, when a load is applied by pressing on the electronic component, the sheet body 2 exhibits stickiness and has excellent workability.

[0097] The thermally conductive sheet 1 is, for example, Figure 4 As shown, a semiconductor device 50 mounted in various electronic devices is sandwiched between a heat source and a heat dissipation member. Figure 4 The semiconductor device 50 shown in the figure has at least an electronic component 51, a heat spreader 52, and a thermally conductive sheet 1, and the thermally conductive sheet 1 is sandwiched between the heat spreader 52 and the electronic component 51. By using the thermally conductive sheet 1, the semiconductor device 50 has high heat dissipation properties, and also has an excellent electromagnetic wave suppression effect according to the content of the magnetic metal powder in the binder resin.

[0098] There is no particular limitation on the electronic component 51, and it can be appropriately selected according to the purpose. Examples thereof include various semiconductor components such as CPU, MPU, graphic computing element, image sensor, antenna element, and battery. There is no particular limitation on the heat spreader 52 as long as it is a component for dissipating the heat generated by the electronic component 51, and it can be appropriately selected according to the purpose. The thermal conductive sheet 1 is clamped between the thermal spreader 52 and the electronic component 51. In addition, the thermal conductive sheet 1 is clamped between the thermal spreader 52 and the heat dissipation device 53, thereby constituting a heat dissipation component for dissipating the heat of the electronic component 51 together with the thermal spreader 52.

[0099] The installation position of the thermally conductive sheet 1 is not limited to between the heat spreader 52 and the electronic component 51, or between the heat spreader 52 and the heat sink 53, and can be appropriately selected according to the configuration of the electronic device or semiconductor device. In addition, as a heat dissipation component, in addition to the heat spreader 52 and the heat sink 53, any heat dissipation component that conducts the heat generated from the heat source to the outside can be used, such as a heat sink, a cooler, a die pad, a printed circuit board, a cooling fan, a Peltier element, a heat pipe, a metal cover, a housing, etc.

[0100] [Workability and reprocessability]

[0101] In addition, the thermally conductive sheet 1 can be reprocessed, that is, it can be peeled off from one end of the electronic component and reattached again for reasons such as correcting positional deviation or disassembling and reassembling after temporary assembly. In this case, the thermally conductive sheet 1 is attached to the electronic component by applying a load when placed on the electronic component, and then, when the thermally conductive sheet is reattached, the load is released, the sheet is peeled off from the electronic component, and is reattached to the electronic component.

[0102] Here, the thermally conductive sheet 1 to which the present technique is applied has a volume ratio of the fibrous thermally conductive filler to the binder resin of 0.6 or less when the binder resin is 1. The fibrous thermally conductive filler protrudes from the surface of the sheet body 2 and is covered with the uncured component of the binder resin.

[0103] Such thermally conductive sheet 1 has a volume ratio of the fibrous thermally conductive filler to the binder resin of 0.6 or less when the binder resin is 1. Thus, even when a load is applied when mounting on electronic components, the sheet body 2 recovers to 90% or more of its thickness when the load is released.

[0104] In addition, the thermally conductive sheet 1 in which the volume ratio of the fibrous thermally conductive filler to the binder resin is less than 0.6 has appropriate softness, and the surface roughness of the cut surface when the thermally conductive molded body is cut into sheets is low, for example, the maximum height Rz value is lower than that of the thermally conductive sheet in which the volume ratio is greater than 0.6. In addition, after the load is applied, the Rz value is further reduced, and the difference in the Rz value before and after the load is applied is larger than that of the thermally conductive sheet in which the volume ratio is greater than 0.6.

[0105] For the thermally conductive sheet 1 having such a low Rz value after release of the load and the above-mentioned 90% or more recovery rate of thickness after release of the load, the length of the fibrous thermally conductive filler protruding from the sheet surface after release of the load is the same as that at the beginning.

[0106] That is, once the thermally conductive sheet 1 is peeled off from the electronic component, the fibrous thermally conductive filler protrudes from the sheet surface again, thereby reducing or eliminating the stickiness. Furthermore, when the sheet body 2 is re-attached, if a load is applied to the sheet body 2 by pressing in advance or by sandwiching between the electronic component and the heat dissipation member, the fibrous thermally conductive filler protruding from the sheet surface is buried in the sheet body 2, and the uncured components of the binder resin carried in the sheet body 2 ooze out, thereby exhibiting stickiness again.

[0107] Therefore, the thermally conductive sheet has good operability and workability because its stickiness is reduced or eliminated before installation even during reprocessing operations, and exhibits stickiness during installation, thereby improving the adhesion with electronic components and heat dissipation members even when the sheet surface has irregularities, thereby achieving a reduction in thermal resistance.

[0108] Such a thermally conductive sheet 1 can also exhibit the same effect not only during the reworking operation but also when a pre-pressing step is provided before the first mounting operation, and has good workability.

[0109] Example

[0110] Next, an example of the present technology is described. In this example, a silicone composition (thermal conductive resin composition) containing aluminum oxide and carbon fiber as a fibrous thermal conductive filler is prepared, and the silicone cured product (thermal conductive molded body) is molded and cut into sheets to obtain a thermal conductive sheet. The obtained thermal conductive sheet is pressed, and the sheet thickness before and after pressing is evaluated. The samples before and after pressing are subjected to 0.8 kgf / cm by a method based on ASTM-D5470. 2 The thermal resistance obtained by the load of , the OO type hardness in the durometer hardness standard ASTM-D2240 before and after pressing, the distance between the carbon fiber and the surface of the thermal conductive sheet before and after pressing, and the surface roughness (Rz value) of the thermal conductive sheet before and after pressing. In addition, the distance between the carbon fiber and the surface of the thermal conductive sheet before and after pressing was measured in 3D (depth direction) using a stereo microscope (KEYENCE VHX-5000) with a magnification of 1000 times.

[0111] [Example 1]

[0112] In Example 1, as shown in Table 1, 46.2% by volume of mixed alumina particles having an average particle size of 1 μm and 5 μm coupled with a silane coupling agent and 14% by volume of pitch-based carbon fibers having an average fiber length of 200 μm were mixed in a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a liquid silicone resin having an organopolysiloxane as a main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 53:47. The total amount of the binder resin in Example 1 is 39.8% by volume, the amount of carbon fibers is 14% by volume, and the volume ratio of carbon fibers to the binder resin is 0.35.

[0113] The obtained silicone composition was extruded into a hollow quadrangular prism-shaped mold (50 mm × 50 mm) to form a 50 mm□ silicone molded body. The silicone molded body was heated in an oven at 100°C for 6 hours to form a silicone cured product. The silicone cured product was cut using a slicer so that the thickness became 1.0 mm to obtain a thermally conductive sheet. Next, the thermally conductive sheet was clamped with a peel-treated PET film and pressed at 87°C, 0.5 MPa, and 3 minutes.

[0114] [Example 2]

[0115] In Example 2, the cured silicone material prepared in Example 1 was cut into pieces with a slicer so as to have a thickness of 2.0 mm, thereby obtaining a thermally conductive sheet. Next, the thermally conductive sheet was sandwiched between PET films subjected to a peeling treatment, and the thermally conductive sheet was pressed under the conditions of 87° C., 0.5 MPa, and 3 minutes. The total amount of the binder resin in Example 2 was 39.8% by volume, the amount of carbon fiber blended was 14% by volume, and the volume ratio of the carbon fiber to the binder resin was 0.35.

[0116] [Example 3]

[0117] In Example 3, the cured silicone material prepared in Example 1 was cut into a thickness of 3.0 mm using a slicer to obtain a thermally conductive sheet. Next, the thermally conductive sheet was sandwiched between PET films subjected to a peeling treatment, and the thermally conductive sheet was pressed under the conditions of 87° C., 0.5 MPa, and 3 minutes. The total amount of the binder resin in Example 3 was 39.8% by volume, the amount of carbon fiber blended was 14% by volume, and the volume ratio of the carbon fiber to the binder resin was 0.35.

[0118] [Example 4]

[0119] In Example 4, as shown in Table 1, 46.2% by volume of mixed alumina particles having an average particle size of 1 μm and 5 μm coupled with a silane coupling agent and 14% by volume of pitch-based carbon fibers having an average fiber length of 200 μm were mixed in a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a liquid silicone resin having an organopolysiloxane as a main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 58:42. The total amount of the binder resin in Example 4 is 39.8% by volume, the amount of carbon fibers is 14% by volume, and the volume ratio of carbon fibers to the binder resin is 0.35.

[0120] The obtained silicone composition was extruded into a hollow quadrangular prism-shaped mold (50 mm × 50 mm) to form a 50 mm□ silicone molded body. The silicone molded body was heated in an oven at 100°C for 6 hours to form a silicone cured product. The silicone cured product was cut using a slicer so that the thickness became 3.0 mm to obtain a thermally conductive sheet. Next, the thermally conductive sheet was clamped with a release-treated PET film and pressed at 87°C, 0.5 MPa, and 3 minutes.

[0121] [Example 5]

[0122] In Example 5, as shown in Table 1, 46.2% by volume of mixed alumina particles having an average particle size of 1 μm and 5 μm coupled with a silane coupling agent and 14% by volume of pitch-based carbon fibers having an average fiber length of 200 μm were mixed in a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a liquid silicone resin having an organopolysiloxane as a main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 50:50. The total amount of the binder resin in Example 5 is 39.8% by volume, the amount of carbon fibers is 14% by volume, and the volume ratio of carbon fibers to the binder resin is 0.35.

[0123] The obtained silicone composition was extruded into a hollow quadrangular prism-shaped mold (50 mm × 50 mm) to form a 50 mm□ silicone molded body. The silicone molded body was heated in an oven at 100°C for 6 hours to form a silicone cured product. The silicone cured product was cut using a slicer so that the thickness became 3.0 mm to obtain a thermally conductive sheet. Next, the thermally conductive sheet was clamped with a release-treated PET film and pressed at 87°C, 0.5 MPa, and 3 minutes.

[0124] [Example 6]

[0125] In Example 6, as shown in Table 1, 36% by volume of mixed alumina particles having an average particle size of 1 μm and 5 μm coupled with a silane coupling agent and 14% by volume of pitch-based carbon fibers having an average fiber length of 200 μm were mixed in a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a liquid silicone resin having an organopolysiloxane as a main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 53:47. The total amount of the binder resin in Example 6 is 50% by volume, the amount of carbon fibers is 14% by volume, and the volume ratio of the carbon fibers to the binder resin is 0.28.

[0126] The obtained silicone composition was extruded into a hollow quadrangular prism-shaped mold (50 mm × 50 mm) to form a 50 mm□ silicone molded body. The silicone molded body was heated in an oven at 100°C for 6 hours to form a silicone cured product. The silicone cured product was cut using a slicer so that the thickness became 3.0 mm to obtain a thermally conductive sheet. Next, the thermally conductive sheet was clamped with a release-treated PET film and pressed at 87°C, 0.5 MPa, and 3 minutes.

[0127] [Example 7]

[0128] In Example 7, as shown in Table 1, 49% by volume of mixed alumina particles having an average particle size of 1 μm and 5 μm coupled with a silane coupling agent and 14% by volume of pitch-based carbon fibers having an average fiber length of 200 μm were mixed in a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a liquid silicone resin having an organopolysiloxane as a main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 53:47. The total amount of the binder resin in Example 7 is 37% by volume, the amount of carbon fibers is 14% by volume, and the volume ratio of carbon fibers to the binder resin is 0.38.

[0129] The obtained silicone composition was extruded into a hollow quadrangular prism-shaped mold (50 mm × 50 mm) to form a 50 mm□ silicone molded body. The silicone molded body was heated in an oven at 100°C for 6 hours to form a silicone cured product. The silicone cured product was cut using a slicer so that the thickness became 3.0 mm to obtain a thermally conductive sheet. Next, the thermally conductive sheet was clamped with a release-treated PET film and pressed at 87°C, 0.5 MPa, and 3 minutes.

[0130] [Example 8]

[0131] In Example 8, as shown in Table 1, 37.2% by volume of mixed alumina particles having an average particle size of 1 μm and 5 μm coupled with a silane coupling agent and 23% by volume of pitch-based carbon fibers having an average fiber length of 200 μm were mixed in a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a liquid silicone resin having an organopolysiloxane as a main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 53:47. The total amount of the binder resin in Example 8 is 39.8% by volume, the amount of carbon fibers is 23% by volume, and the volume ratio of carbon fibers to the binder resin is 0.58.

[0132] The obtained silicone composition was extruded into a hollow quadrangular prism-shaped mold (50 mm × 50 mm) to form a 50 mm□ silicone molded body. The silicone molded body was heated in an oven at 100°C for 6 hours to form a silicone cured product. The silicone cured product was cut using a slicer so that the thickness became 3.0 mm to obtain a thermally conductive sheet. Next, the thermally conductive sheet was clamped with a release-treated PET film and pressed at 87°C, 0.5 MPa, and 3 minutes.

[0133] [Example 9]

[0134] In Example 9, as shown in Table 1, 48.2% by volume of mixed alumina particles with average particle sizes of 1 μm and 5 μm coupled with a silane coupling agent and 12% by volume of pitch-based carbon fibers with an average fiber length of 200 μm were mixed in a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a liquid silicone resin having an organopolysiloxane as a main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 53:47. The total amount of the binder resin in Example 9 is 39.8% by volume, the amount of carbon fiber is 12% by volume, and the volume ratio of carbon fiber to the binder resin is 0.30.

[0135] The obtained silicone composition was extruded into a hollow quadrangular prism-shaped mold (50 mm × 50 mm) to form a 50 mm□ silicone molded body. The silicone molded body was heated in an oven at 100°C for 6 hours to form a silicone cured product. The silicone cured product was cut using a slicer so that the thickness became 3.0 mm to obtain a thermally conductive sheet. Next, the thermally conductive sheet was clamped with a release-treated PET film and pressed at 87°C, 0.5 MPa, and 3 minutes.

[0136] [Comparative Example 1]

[0137] In Comparative Example 1, as shown in Table 1, 42.5% by volume of mixed alumina particles having an average particle size of 4 μm coupled with a silane coupling agent and 23% by volume of pitch-based carbon fibers having an average fiber length of 150 μm were mixed in a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin uses a liquid silicone resin having an organopolysiloxane as a main component, and is formulated in a manner such that the ratio of silicone agent A to agent B is 53:47. The total amount of the binder resin in Comparative Example 1 is 34.1% by volume, the amount of carbon fibers is 23% by volume, and the volume ratio of carbon fibers to the binder resin is 0.67.

[0138] The obtained silicone composition was extruded into a hollow quadrangular prism-shaped mold (50 mm × 50 mm) to form a 50 mm□ silicone molded body. The silicone molded body was heated in an oven at 100°C for 6 hours to form a silicone cured product. The silicone cured product was cut using a slicer so that the thickness became 1.0 mm to obtain a thermally conductive sheet. Next, the thermally conductive sheet was clamped with a peel-treated PET film and pressed at 87°C, 0.5 MPa, and 3 minutes.

[0139] [Comparative Example 2]

[0140] In Comparative Example 2, the silicone cured product prepared in Comparative Example 1 was cut into a thickness of 2.0 mm using a slicer to obtain a thermally conductive sheet. Next, the thermally conductive sheet was sandwiched between PET films subjected to a peeling treatment, and the thermally conductive sheet was pressed under the conditions of 87° C., 0.5 MPa, and 3 minutes. The total amount of the binder resin in Comparative Example 2 was 34.1% by volume, the amount of carbon fiber blended was 23% by volume, and the volume ratio of the carbon fiber to the binder resin was 0.67.

[0141] [Comparative Example 3]

[0142] In Comparative Example 3, the silicone cured product prepared in Comparative Example 1 was cut into a thickness of 3.0 mm using a slicer to obtain a thermally conductive sheet. Next, the thermally conductive sheet was sandwiched between PET films subjected to a peeling treatment, and the thermally conductive sheet was pressed under the conditions of 87° C., 0.5 MPa, and 3 minutes. The total amount of the binder resin in Comparative Example 3 was 34.1% by volume, the amount of carbon fiber blended was 23% by volume, and the volume ratio of the carbon fiber to the binder resin was 0.67.

[0143] [Comparative Example 4]

[0144] In Comparative Example 4, as shown in Table 1, 70.6% by volume of aluminum nitride particles having an average particle size of 1 μm, 5.2% by volume of aluminum hydroxide particles having an average particle size of 5 μm, and 3.3% by volume of aluminum oxide particles having an average particle size of 4 μm were mixed with a two-component addition reaction type liquid silicone to prepare a silicone composition. The two-component addition reaction type liquid silicone resin used a liquid silicone resin having an organopolysiloxane as a main component, and was blended so that the blending ratio of silicone agent A to agent B was 58:42.

[0145] The obtained silicone composition was sandwiched between release-treated PET, applied to a thickness of 1 mm using a bar coater, and heated in an oven at 100° C. for 6 hours to obtain a thermally conductive sheet.

[0146] [Comparative Example 5]

[0147] In Comparative Example 5, the same conditions as in Comparative Example 4 were employed except that the obtained silicone composition was sandwiched between release-treated PET and applied with a bar coater to a thickness of 2 mm as shown in Table 1.

[0148] [Comparative Example 6]

[0149] In Comparative Example 6, the same conditions as in Comparative Example 4 were employed except that the obtained silicone composition was sandwiched between release-treated PET and applied with a bar coater to a thickness of 3 mm as shown in Table 1.

[0150] [Table 1]

[0151]

[0152] [Table 2]

[0153]

[0154] As shown in Table 1, in the thermally conductive sheets involved in Examples 1-9, the volume ratio of the fibrous thermally conductive filler to the binder resin is small, less than 0.6, so the value of the OO type in the durometer hardness standard ASTM-D2240 is 15 to 40, which is lower than that of Comparative Examples 1-3. In addition, the Rz value is improved after pressing, and the recovery rate of the sheet thickness is more than 90%. Therefore, in the thermally conductive sheets involved in Examples 1-9, the length of the carbon fibers protruding from the sheet surface before and after pressing is 60 μm, and there is no change before and after pressing. Among them, the thermally conductive sheets involved in Examples 1-9 were subjected to 0.3 kgf / cm 2 The thermal resistance is 1.9℃cm when the load 2 / W or less.

[0155] The thermally conductive sheets involved in Examples 1 to 9 themselves have no stickiness, but when pressed on a glass plate with a finger, they show stickiness and can be confirmed to be closely attached to the glass. Therefore, according to Examples 1 to 9, it can be seen that the following thermally conductive sheets are obtained: the stickiness of the sheet surface is reduced or eliminated before installation, the handling and workability are excellent, the stickiness is shown by pressing, the close adhesion to electronic components is excellent, the thermal resistance is reduced, and the reworkability is possible.

[0156] On the other hand, in the thermally conductive sheet according to Comparative Example 1-3, the volume ratio of the fibrous thermally conductive filler to the binder resin was greater than 0.6, and the value of the OO type in the durometer hardness standard ASTM-D2240 was also high, 55. In addition, although the Rz value after pressing was improved, the recovery rate of the sheet thickness was less than 90%, and the length of the carbon fiber protruding from the sheet surface was short, 10 μm. Therefore, a sticky feeling remained, and the reprocessability was poor.

[0157] Explanation of symbols

[0158] 1 thermally conductive sheet, 2 sheet body, 10 fibrous thermally conductive filler.

Claims

1. A thermally conductive sheet comprising a sheet body formed by curing a binder resin, wherein the binder resin contains at least a polymer matrix component and a fibrous thermally conductive filler, The volume ratio of the fibrous thermally conductive filler to the binder resin is 0.6 or less when the binder resin is set to 1. The fibrous thermally conductive filler protrudes from the surface of the sheet body and is covered with an uncured component of the binder resin. 2 . The thermally conductive sheet according to claim 1 , wherein a length of the thermally conductive filler protruding from the surface of the sheet body is longer than 50 μm. 3 . The thermally conductive sheet according to claim 1 , wherein the thermally conductive filler is oriented in a thickness direction of the sheet body. 4 . The thermally conductive sheet according to claim 1 , wherein the value of type OO in durometer hardness standard ASTM-D2240 is 15 to 40.

5. The thermally conductive sheet according to any one of claims 1 to 3, wherein the sheet body is heated at 0.8 kgf / cm 2 The sheet body is compressed by a load, and after the load is released, the thickness of the sheet body recovers to more than 90% of that before compression. 6 . The thermally conductive sheet according to claim 1 , wherein a load is applied to the sheet body to compress it, and after the load is released, a difference in surface roughness Rz between before and after the load is applied is 8 or less.

7. The thermally conductive sheet according to any one of claims 1 to 3, wherein 0.3 kgf / cm 2 The thermal resistance under load is 1.9℃cm 2 / W or less.

8. A method for producing a thermally conductive sheet, comprising the following steps: A step of forming a thermally conductive molded body by molding a thermally conductive resin composition containing a fibrous thermally conductive filler in a binder resin into a predetermined shape and curing the composition; and a step of cutting the thermally conductive molded body into sheets to form a thermally conductive sheet, The volume ratio of the fibrous thermally conductive filler to the binder resin is 0.6 or less when the binder resin is set to 1. The fibrous thermally conductive filler protrudes from the surface of the thermally conductive sheet body and is covered with an uncured component of the binder resin. 9 . The method for producing a thermally conductive sheet according to claim 8 , wherein the thermally conductive sheet is pressed to cause uncured components of the binder resin to ooze out.

10. A method for mounting a thermally conductive sheet, the method comprising the steps of: placing the thermally conductive sheet on an electronic component and sandwiching the thermally conductive sheet between the electronic component and a heat dissipation member; When placed on the electronic component, a load is applied to the thermally conductive sheet to cause the sheet to exhibit adhesiveness and adhere to the electronic component; and When reattaching the thermally conductive sheet, the load is released, the sheet is peeled off from the electronic component, and the sheet is attached to the electronic component again. The thermally conductive sheet has a sheet body formed by curing a binder resin, wherein the binder resin contains at least a polymer matrix component and a fibrous thermally conductive filler. The volume ratio of the fibrous thermally conductive filler to the binder resin is 0.6 or less when the binder resin is set to 1. The fibrous thermally conductive filler protrudes from the surface of the sheet body and is covered with an uncured component of the binder resin.

Citation Information

Patent Citations

  • Thermally conductive sheet and method of producing the same

    JP2012023335A

  • Manufacturing method of heat conductive sheet, heat conductive sheet, and heat radiation member

    JP2015029075A

  • Manufacturing method of heat conductive sheet, heat conductive sheet, and heat radiation member

    JP2015029076A

  • Vertical injection molding apparatus and method of producing resin product using the same

    JP2018134769A

  • Heat conduction sheet, heat conduction sheet manufacture method, heat radiation member, and semiconductor device

    CN106796926A